Blind Men and the Elephant - Hasu, Mervi (Outlines. Critical Practice Studies, 2000)
I suggest that the transformation of an artifact from an introductory-type instrument into a viable, collectively used tool cannot be understood solely in terms of gradual adaptation of the technology and user environment, but also as a qualitatively broader integration process in which an expansion takes place. The case illustrated a constrained shift of an artifact from its first adopter, an individual pioneer user, to a more collective user in institutional medicine. The artifact, a neuromagnetometer instrument for brain research and diagnostics, brings together physicists, neuroscientists, physicians as well as various practitioners from the medical imaging industry. I applied an activity-theoretical framework for analysing the adoption of the neuromagnetometer from the pioneer phase of implementation into the more established use. The case showed that the anticipated transformation of the artifact constituted a major challenge for the user organization and its practitioners. It is suggested that an expansion of the object into a shared object of implementation among the separate practitioner groups is indispensable.This expansion of the object involves for the practitioners to recognize both the different objects and requirements of the pioneer phase of the implementation and the new phase of introduction into medical practice. It is shown that this recognition does not, however, come as given, spontaneously born in the transition. The emerging new object may remain only partially shared if not made visible by deliberate effort among the practitioners. The expansion requires collective visualization of the work and reflective dialogue on it. Employing analytical tools, such as the activity-theoretical concepts used here, is one possible way of facilitating such an effort.